Characteristics of Liquefaction in Embankment Models Reinforced with Hybrid Piles - Muhammad Yunus; Achmad B. Muhiddin; Tri Harianto; Ardy Arsyad (Salehan Institute of Higher Education, 2026)
Liquefaction of saturated loose sand poses a serious threat to the stability of embankments subjected to seismic loading. This study aims to evaluate the effectiveness of an innovative and environmentally friendly liquefaction mitigation technique using hybrid piles (HPs) that combine structural stiffness and vertical drainage functions. A series of 1-g shaking table tests was conducted on embankment models constructed over saturated sand with an initial relative density of 40%. The models were subjected to repeated sinusoidal seismic excitations with peak ground accelerations (PGA) ranging from 0.3 g to 0.5 g. The performance of the HPs system was assessed by analyzing cone penetration resistance, acceleration response, excess pore water pressure ratio, changes in relative density and void ratio, and surface settlement. The experimental results demonstrate that the HPs system significantly enhances soil densification and stiffness, as indicated by a 1.3–3.0-fold increase in penetration resistance and a relative density increase of up to 7–10% in deeper layers. The HPs system reduced the maximum excess pore water pressure ratio by up to 16.26%, thereby delaying liquefaction onset and enhancing pore pressure dissipation under repeated seismic loading. In addition, settlement was reduced by approximately 37–42% compared with the unreinforced model across all PGA levels. The novelty of this study lies in the integrated use of locally sourced timber and prefabricated vertical drains within a single reinforcement element, providing combined mechanical reinforcement and drainage enhancement. These findings confirm that HPs offer a sustainable and effective solution for mitigating liquefaction and controlling deformation in embankment foundations under seismic conditions.